Advancing oral health policy through persuasive messaging and effective research measures. (1st November 2020) - Burgette, Jacqueline M.; Vujicic, Marko; Booth, Meg; Meltzer, David; Best, Thomas J.; Neill, James; Conicella, Mary Lee; Joskow, Renée W.; Chalmers, Natalia I.
Abstract: Oral health is often excluded from broad health policy discussions, addressed only in a policy silo. There is a paucity of research to guide policymaking as it relates to oral health. In response, AcademyHealth's Oral Health Interest Group organized a meeting during the 2019 AcademyHealth Annual Research Meeting to promote transdisciplinary dialog on the current state of oral health policy and the steps necessary to improve the oral health of Americans. This article summarizes the two main themes that emerged from the proceedings of the Oral Health Interest Group meeting: a) recommendations for advocating the inclusion of oral health in policy discussions and b) critical research topics and measures needed for effective oral health policies in the future.